Water stress reduces cellulose deposition in the cell wall and increases wax content, resulting in decreased fiber quality - Yongchao Han; Yi Yang; Han Luo; Jinhui Cui; Bifu Kuang; Xinyu Zhang; Jie Sun; Jian Wei Xu; Feng Liu (Frontiers in Plant Science, 2025)
IntroductionWater deficiency reduces cotton fiber quality, but the underlying mechanisms behind this decline remain poorly understood. Although the cuticle is critical for plant water homeostasis under drought, few studies have addressed the relationship between water stress, fiber epidermal wax, and fiber quality. Thus, studying the interaction between fiber cuticular wax and quality is crucial for understanding plant drought tolerance and breeding superior drought-resistant cotton varieties.MethodsThis experiment was designed as a randomized block design. Two cotton cultivars, Xincaimian7 (XC7, with high cuticular wax) and Shidamian217 (SD217, with low cuticular wax), were selected as materials. Two irrigation regimes were applied: well-watered (WW) and water-deficit (WD), each with three independent biological replicates.ResultsResults showed WD irrigation significantly reduced the cotton fiber accumulation rate, particularly between 25-30 days post-anthesis (DPA). Compared with WW irrigation, the rate decreased by 23.62% and 30.82% respectively. WD treatment significantly inhibited the expression of the genes encoding sucrose synthase GhSusy and cellulose synthase GhCesA in cotton fibers. At 30 DPA, compared to the WW treatment, the sucrose contents in SD217 and XC7 fibers decreased by 18.66% and 12.85%, while cellulose contents dropped by 9.91% and 17.17%, respectively, resulting in a significant decrease in the thickness of the cell walls by 10.59% and 9.50% respectively. However, the WD treatment significantly induced the expression of wax synthesis-related genes in cotton fibers. Compared with the WW treatment, at 30 DPA, the epidermal wax contents of the fibers of SD217 and XC7 increased significantly by 81.87% and 97.34%, respectively. Correlation analysis reveals a significant positive relationship between fiber strength, length, and the contents of cellulose and sucrose (p<0.01). Conversely, a significant negative correlation exists between these fiber properties and wax content (p<0.01).DiscussionIn summary, WD reduces the sucrose content in cotton fibers and induces wax accumulation. Thinner cell walls combined with a thicker wax layer altered the mechanical properties of the fibers, thus leading to a decrease fiber quality. Therefore, when breeding drought-tolerant varieties, breeders need to balance the drought resistance with the sucrose and wax characteristics of the fibers.